Предмет: Алгебра,
автор: 1036
Пожалуйста, помогите с производными
Приложения:
Ответы
Автор ответа:
0
а) f(x) = 2x-3
x+1
f(x)' = (2x-3)' (x+1) - (2x-3) (x+1)' = 2(x+1) - (2x-3) = 2x+2-2x+3 = 5
(x+1)² (x+1)² (x+1)² (x+1)²
г) f(x)=√(4x-2)
f(x)' = 1 * (4x-2)' = 4 = 2
2√(4x-2) 2√(4x-2) √(4x-2)
x+1
f(x)' = (2x-3)' (x+1) - (2x-3) (x+1)' = 2(x+1) - (2x-3) = 2x+2-2x+3 = 5
(x+1)² (x+1)² (x+1)² (x+1)²
г) f(x)=√(4x-2)
f(x)' = 1 * (4x-2)' = 4 = 2
2√(4x-2) 2√(4x-2) √(4x-2)
Автор ответа:
0
а)
б)
в)
г)
б)
в)
г)
Похожие вопросы
Предмет: Музыка,
автор: DiSemka
Предмет: Немецкий язык,
автор: nubipro33100
Предмет: Биология,
автор: viktoriagerasimova84
Предмет: Химия,
автор: Julua07